2021
DOI: 10.1101/2021.08.24.21262516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex differences in incidence and mortality of bloodstream infections. Results from the population-based HUNT study in Norway

Abstract: ObjectiveTo examine the effect of sex on risk of bloodstream infections (BSI) and BSI mortality and to assess to what extent known risk factors for BSI mediate this association in the general population.ParticipantsThe prospective, population-based HUNT2 Survey (1995-97) in Norway invited 93,898 inhabitants ≥20 years in the Nord-Trøndelag region, whereof 65,237 (69.5%) participated. 46.8% of the participants were men.ExposuresSex and potential mediators between sex and BSI; health behaviours (smoking, alcohol … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
(79 reference statements)
1
3
0
Order By: Relevance
“…13 Another possible explanation includes differences in immune responses based on genetic and hormonal factors. 14 Cirrhosis was also associated with an increased risk of bacteremia in our study. Prior studies have consistently identified cirrhosis as a risk factor for bacteremia, with incidence 10 times higher in cirrhotic versus non-cirrhotic patients.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…13 Another possible explanation includes differences in immune responses based on genetic and hormonal factors. 14 Cirrhosis was also associated with an increased risk of bacteremia in our study. Prior studies have consistently identified cirrhosis as a risk factor for bacteremia, with incidence 10 times higher in cirrhotic versus non-cirrhotic patients.…”
Section: Discussionsupporting
confidence: 67%
“…13 Another possible explanation includes differences in immune responses based on genetic and hormonal factors. 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether insomnia is associated with the risk of other and more severe invasive infections, such as bloodstream infections (BSIs) is not clear. BSI is a serious infectious disease, rating among top seven causes of deaths in Europe and North America (Goto & Al-Hasan, 2013), men are more at risk (Randi Marie Mohus et al, 2021), and BSI often leads to sepsis (Laupland et al, 2005). Sepsis is defined as a dysregulated host response to infection, estimated to annually afflict 48.9 million people and cause 11 million deaths worldwide (Rudd et al, 2020).…”
Section: Introductionmentioning
confidence: 99%